2021
DOI: 10.1038/s41598-021-01265-8
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic experimental comparison of particle filtration efficiency test methods for commercial respirators and face masks

Abstract: Respirators, medical masks, and barrier face coverings all filter airborne particles using similar physical principles. However, they are tested for certification using a variety of standardized test methods, creating challenges for the comparison of differently certified products. We have performed systematic experiments to quantify and understand the differences between standardized test methods for N95 respirators (NIOSH TEB-APR-STP-0059 under US 42 CFR 84), medical face masks (ASTM F2299/F2100), and COVID-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…This test aerosol has also formed the basis for a number of recent research works, e.g. 2 8 ,. A roughly monodisperse polystyrene latex (PSL) aerosol having a mobility diameter of 100 nm.…”
Section: Background and Summarymentioning
confidence: 98%
See 2 more Smart Citations
“…This test aerosol has also formed the basis for a number of recent research works, e.g. 2 8 ,. A roughly monodisperse polystyrene latex (PSL) aerosol having a mobility diameter of 100 nm.…”
Section: Background and Summarymentioning
confidence: 98%
“…Comparably few research studies have considered this challenge aerosol – e.g. 2 , 8 , 11 14 , – with results being more variable, given the lack of neutralization 8 .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the neutralized to uncharged case, 180 we confirmed that the variation of net charge in the neutralized distribution was negligible (see 181 Supplemental Information A). It is important to note that the natural charge distribution produced 182 by a nebulizer will result in the measurement of a higher PFE than that measured for neutralized 183 particles (Corbin et al, 2021), which can be a reason for differences in PFE between studies. The 184 remaining tests were run without the DMA column.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Considering typical mask flow areas, this 195 corresponds to an inhalation flow of ~50 L min -1 , midway between a resting rate and that used for 196 N95 testing (Caretti et al, 2004). Higher face velocities would yield larger PFEs for particles above 197 several microns due to increased impaction, but lower PFE for the smallest particles captured by 198 electrostatic interactions (Corbin et al, 2021)…”
Section: A C C E P T Ementioning
confidence: 99%